Análisis del sector financiero popular y solidario del Cantón Colta Provincia de Chimborazo en el período 2019 – 2020. - Niño Rodríguez, Alejandro (2021)
This dissertation seeks to demonstrate the generated scope by the popular and solidarity economy in the Colta canton, in terms of financial inclusion and the perception of citizens regarding its different products and services. To measure this management capacity the financial analysis was used. In terms of perception, surveys were used for both microentrepreneurs and individuals who measured their satisfaction with the bank; The information was collected through the SEPS control entity and processed based on the proposed models by the World Council of Credit Unions (WOCCU) and the Global Findex. This study allowed to realize how this new economy presents a greater participation than that maintained by the traditional financial system; however, it still has shortcomings in terms of coverage and quality, mostly due to poor investment practice and credit management.